2022
DOI: 10.1177/10634266221100212
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Bidirectional Language–Behavior Influences for Spanish–English Dual Language Learning Children in Head Start

Abstract: The purpose of this exploratory study was to examine the longitudinal, bidirectional relations between receptive and expressive Spanish and English language and internalizing and externalizing behavior problems in a sample of 97 preschool children from Spanish-speaking, homes who were enrolled in a Head Start program. Eight cross-lagged path models were conducted: four for each language. Models tested the autoregressive and cross-lagged paths between two dimensions of language (expressive and receptive) and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Gigi An et al (2021) found that internalizing behavioral problems predicted later language but not vice versa. Based on a sample of 97 preschool Spanish-speaking children, Juhasz and Boyce (2023) found that after controlling for age, gender, and maternal education, internalizing behavioral problems predicted later language (receptive vocabulary) but not vice versa. Most recently, Tamayo et al (2024) used the longitudinal data from the Millennium Cohort Study in the United Kingdom with 10,878 children followed from 3 to 11 years old.…”
Section: Mutualism Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Gigi An et al (2021) found that internalizing behavioral problems predicted later language but not vice versa. Based on a sample of 97 preschool Spanish-speaking children, Juhasz and Boyce (2023) found that after controlling for age, gender, and maternal education, internalizing behavioral problems predicted later language (receptive vocabulary) but not vice versa. Most recently, Tamayo et al (2024) used the longitudinal data from the Millennium Cohort Study in the United Kingdom with 10,878 children followed from 3 to 11 years old.…”
Section: Mutualism Theorymentioning
confidence: 99%
“…Regarding the possible mutualistic coupling of language and behavioral problems, it is likely that limited linguistic abilities may impede language-based self-regulation, which may lead to the internalization of behavioral problems such as withdrawal, anxiety, depression, and dysphoria and the externalization of behavioral problems such as defiance, impulsivity, aggression, antisociality, and overactivity (Bornstein et al, 2013). In return, behavioral problems reduce opportunities for using language in the context of rich educational environments, whether with peers or teachers, and thus impede children’s ability to engage in academic and social settings that promote linguistic development (Cunningham et al, 2022; Juhasz & Boyce, 2023).…”
Section: Mutualism Theorymentioning
confidence: 99%